Macroeconomic Interactions in Nigeria: VECM-Based Analysis (2001-2023) - Olaniyan Joseph Olawale; Adetunkasi Taiwo Flora; Aladesuyi Alademomi (Darul Yasin Al Sys, 2026)
Understanding the dynamic relationships among major macroeconomic variables is essential for evaluating economic stability and informing policy design in developing economies such as Nigeria. This study aimed to investigate the interrelationships among Gross Domestic Product (GDP), inflation, broad money supply (M2), interest rate, exchange rate, and unemployment in Nigeria over the period 2001–2023. Annual data were obtained from the Central Bank of Nigeria, World Bank, International Monetary Fund, and CEIC databases and analyzed using a Vector Error Correction Model (VECM) implemented in Python’s statsmodels framework to capture both short-run adjustments and long-run equilibrium dynamics. The findings reveal the presence of three stable long-run cointegrating relationships among the variables. Inflation was found to respond strongly to changes in GDP, interest rates, and exchange-rate movements, whereas the effects of money supply and unemployment were relatively weaker. The results further indicate that economic growth contributes to modest reductions in unemployment, while persistent inflationary pressures and volatile interest rates tend to worsen labor-market outcomes. Exchange-rate depreciation also emerged as a major source of macroeconomic instability. Diagnostic tests suggest that the estimated model is broadly robust, although mild indications of serial correlation and multicollinearity remain. The study concludes that Nigeria’s macroeconomic environment is shaped by deep structural weaknesses that require stronger policy coordination, improved exchange-rate management, and sustained structural reforms to enhance price stability and employment outcomes. These findings contribute empirical evidence on long-run and short-run macroeconomic interactions in Nigeria and provide policy-relevant insights for strengthening economic management.